Mapping of Potential Intrusion at Coastal Zone in Small Island Using GIS (Study case: North Sangadji Village) - Nani Nagu; Mohamad Ridwan Lessy; Rachim Achmad; Chandra Chandra (ICETIA, 2016)
A systematic study has been carried out to explore the physicochemical characteristics and Water Quality of groundwater in thirteen chosen sampling stations at Sangadji village North Ternate District in Ternate Island. Water sample from wells in various sites were collected during March to August 2015 and analyzed physicochemical characteristics like EC, Salinity, pH and TDS. The remaining sampling sites show that the several wells in the study area had been an intrusion by saltwater and are not fit for drinking purpose. Furthermore, our integrated study represents a contribution to the future programs for the protection, planning, and management of the terrestrial and marine resources in this coastal area